The dragon in medieval East Christian and Islamic art - Kuehn, Sara. (Islamic History and Civilization, 2011)
This book is a pioneering work on a key iconographic motif, that of the dragon. It examines the perception of this complex, multifaceted motif within the overall intellectual and visual universe of the medieval Irano-Turkish world. Using a broadly comparative approach, the author explores the ever-shifting semantics of the dragon motif as it emerges in neighbouring Muslim and non-Muslim cultures. The book will be of particular interest to those concerned with the relationship between the pre-Islamic, Islamic and Eastern Christian (especially Armenian) world. The study is fully illustrated, with 209 (b/w and full colour) plates, many of previously unpublished material. Illustrations include photographs of architectural structures visited by the author, as well as a vast collection of artefacts, all of which are described and discussed in detail with inscription readings, historical data and textual sources.